Adjustment of Host Cells for Accommodation of Symbiotic Bacteria: Vacuole Defunctionalization, HOPS Suppression, and TIP1g Retargeting in Medicago . Issue 9 (12th September 2014) - Gavrin, Aleksandr; Kaiser, Brent N.; Geiger, Dietmar; Tyerman, Stephen D.; Wen, Zhengyu; Bisseling, Ton; Fedorova, Elena E.
Abstract : The accommodation of thousands of nitrogen-fixing rhizobia in legume root nodules requires changes in functionality of the vacuoles of infected cells. Suppression of HOPS tethering complex genes and tonoplast aquaporin retargeting to symbiosomes is part of the underlying mechanism. Defunctionalization of host vacuoles contributes to the expansion and maintenance of intracellular rhizobia. Abstract: In legume–rhizobia symbioses, the bacteria in infected cells are enclosed in a plant membrane, forming organelle-like compartments called symbiosomes. Symbiosomes remain as individual units and avoid fusion with lytic vacuoles of host cells. We observed changes in the vacuole volume of infected cells and thus hypothesized that microsymbionts may cause modifications in vacuole formation or function. To examine this, we quantified the volumes and surface areas of plant cells, vacuoles, and symbiosomes in root nodules of Medicago truncatula and analyzed the expression and localization of VPS11 and VPS39, members of the HOPS vacuole-tethering complex. During the maturation of symbiosomes to become N2 -fixing organelles, a developmental switch occurs and changes in vacuole features are induced. For example, we found that expression of VPS11 and VPS39 in infected cells is suppressed and host cell vacuoles contract, permitting the expansion of symbiosomes. Trafficking of tonoplast-targeted proteins in infected symbiotic cells is also altered, as shown by retargeting of the aquaporin TIP1g from the tonoplast membrane to the symbiosome membrane. This retargeting appears to be essential for the maturation of symbiosomes. We propose that these alterations in the function of the vacuole are key events in the adaptation of the plant cell to host intracellular symbiotic bacteria.